2009
DOI: 10.3390/ijms10094088
|View full text |Cite
|
Sign up to set email alerts
|

Eu-Doped BaTiO3 Powder and Film from Sol-Gel Process with Polyvinylpyrrolidone Additive

Abstract: Transparent BaTiO3:Eu3+ films were prepared via a sol-gel method and dip-coating technique, using barium acetate, titanium butoxide, and polyvinylpyrrolidone (PVP) as modifier viscosity. BaTiO3:Eu3+ films ~500 nm thick, crystallized after thermal treatment at 700 ºC. The powders revealed spherical and rod shape morphology. The optical quality of films showed a predominant band at 615 nm under 250 nm excitation. A preliminary luminescent test provided the properties of the Eu3+ doped BaTiO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…It was also determined that tensile stress was larger in samples with smaller grains and it can be released by annealing to obtain larger BaTiO 3 grains . Furthermore, the shift of Raman band positions in the fine grained powder spectrum could be attributed to internal stress from surface tension in the nanocrystals, as well . Our investigations have shown that the change in position of the A 1 (2TO) mode and Raman peak at 520 cm −1 , with increase in activation time, follows the same trend [Fig.…”
Section: Resultssupporting
confidence: 60%
“…It was also determined that tensile stress was larger in samples with smaller grains and it can be released by annealing to obtain larger BaTiO 3 grains . Furthermore, the shift of Raman band positions in the fine grained powder spectrum could be attributed to internal stress from surface tension in the nanocrystals, as well . Our investigations have shown that the change in position of the A 1 (2TO) mode and Raman peak at 520 cm −1 , with increase in activation time, follows the same trend [Fig.…”
Section: Resultssupporting
confidence: 60%
“…The parameters of the model have been used for the ES (electrical) and the MS (magnetic) systems: J 1 = 0.8 K, J 2 = −0.5 K, Ω = 5 K , and the bare phonon frequency (i.e. harmonic phonon frequency) ω 0 = 253 cm −1 [8,16], (4) = −2.5 cm −1 , the spin P = 3.5 and the pseudo-spin S = 0.5. These parameters can produce T C = 213 K and T N = 1.9 K. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is difficult to achieve thick films without cracking along the ideal thickness in order to satisfy practical applications. A possible alternative is the incorporation of a high boiling point reagent into the sol such as the polyvinylpyrrolidone (PVP), which has been employed in luminescent systems such as Gd 2 O 3 :Eu 3+ [ 22 ], GdTaO 4 :Eu 3+ [ 23 ] and BaTiO 3 :Eu 3+ [ 24 ]. A different alternative is to add Pluronic F127 acid, a PEO 106 PPO 70 PEO 106 (PEO = polyethylene oxide, PPO = polypropylene oxide) tri-block copolymer with an average molecular weight of 13600 g mol −1 , which has also been found to act as a structure-directing agent in TiO 2 [ 25 , 26 , 27 ] in catalytic and solar cells applications.…”
Section: Introductionmentioning
confidence: 99%